Catalytic Decomposition Of Volatile Organic Compund VOC Pollutants In Air Stream Over Chromium Exchanged Zeolites. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2002)
The catalytic activity and stability studies ofchromium exchanged beta (Cr-BEA),mordenite (Cr-MOR) and ZSM-5 (Cr-ZSM-5) zeolites of different Si/Al ratios for VOCs decomposition are reported.